2018
DOI: 10.1002/ijfe.1683
|View full text |Cite
|
Sign up to set email alerts
|

Does financial market growth improve income distribution? A comparison of developed and emerging market economies of the global sample

Abstract: The objective of this research is to investigate the effects of stock market indicators, banking, and foreign direct investment inflows on income inequalities in developed and emerging market economies around the world. For this reason, the study utilizes annual data that range from 1981 to 2014 on the selected indicators. Given the nature of our variables, we employ panel autoregressive distributed lag models to explore the long‐run estimates of income inequalities. The long‐run estimates indicate that the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Hence, an improved financial system, such as banking and stock market development, will not always benefit poor people. However, a recent study by Paramati and Nguyen (2019) documented that the growth in banking credit helps to minimize the income inequality across the panels of developed and emerging economies. Nonetheless, authors suggested that the growth in stock market indicators has positive and negative effects on income inequality for developed and emerging economies, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, an improved financial system, such as banking and stock market development, will not always benefit poor people. However, a recent study by Paramati and Nguyen (2019) documented that the growth in banking credit helps to minimize the income inequality across the panels of developed and emerging economies. Nonetheless, authors suggested that the growth in stock market indicators has positive and negative effects on income inequality for developed and emerging economies, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovation is an important variable showing the technological ability of a country. In addition, some predict that countries welfare levels are increased by the positive impact of innovation on workforce, productivity and employment capacity (Feldmann, 2013a(Feldmann, , 2013bParamati & Nguyen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the total bank credit, the results of their study suggest that an increase in the raised capital from the stock market reduces income inequality, whereas a rise of turnover in the stock market augments income inequality, and that financial structure affects income inequality by influencing the development of medium-sized enterprises. Paramati and Nguyen, (2019) studied the effects of the stock market, banking sector, and foreign direct investment indicators on income inequalities in developed and emerging market economies around the world from 1981 to 2014. By applying models of lag distributed autoregressive on the panel to explore long-term estimates of income inequalities, they found that long-term estimates indicate that stock market indicators have a significant positive and negative impact on income inequalities in developed and emerging market economies, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a financial perspective, the stock market is the most important market in relation to corporate investment decisions (Paramati and Nguyen, 2019). In addition, going public allows companies to access more financial capital that can fuel innovation (Wies and Moorman, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation